Myosin inhibition enhances cardiomyocyte cell cycle activity through SIRT1-NFAT-mediated H3K9me3 modification - Rui Jiang; Jiayu Chen; Lijuan Pei; Shiqi Huang; Mengying Feng; Zhaohui Ouyang; Min Yuan; Yalin Zhu; Su Yao; Fenglian He; Hongjie Zhang; Xin Dong; et al. (European Journal of Cell Biology)
The limited regenerative capacity in adult mammalian heart is mainly attributed to the low cell cycle activity of cardiomyocytes. Achieving cardiomyocyte division is a challenging undertaking, as the contractile function, a major characteristic of cardiomyocytes, is not overall compatible with cell cycle progression. To dissect the relationship between sarcomeric contraction and proliferation in cardiomyocytes, we utilized Blebbistatin (Blebb), a Myosin II inhibitor commonly used for cardiomyocyte culture ex vivo, and revealed that Myosin inhibition by Blebb in cardiomyocytes resulted in enhanced cell cycle entry with cytokinesis failure, thus increasing polyploidy. Elevated H3K9me3 modification was found to be required for the increased cell cycle entry induced by Blebb, and the increased H3K9me3 modifications were enriched on genes that encode negative regulators of cell cycle and controlled by NFAT transcription factors. Furthermore, SIRT1 was identified to be a nucleocytoplasmic shuttling protein that dissociates from Z lines of sarcomeres and translocates into the nucleus upon Myosin inhibition, directly interacts with NFATc3, and is required for the Blebb-induced elevation of H3K9me3 modification and cell cycle activity. Our results identified a signaling pathway transducing sarcomeric signals to epigenetic modifications modulating the cardiomyocyte cell cycle, which may facilitate the understanding of the complex regulatory network controlling cardiomyocyte proliferation and provide therapeutic targets for regenerative medicine.